Double trouble: A Combined Ovarian and Axial Torsion of Uterus - Varadarajan, R; Shivalingaiah, N (Nepal Journal of Obstetrics and Gynaecology, 2014)
Torsion of the uterus is rare and mainly involves pregnant uterus. A combination of ovarian torsion with an axial torsion of uterus in a non-gravid woman is extremely rare. The exact incidence of uterine torsion is not clearly established, as only few case reports are available in the literature. Usually this kind of torsion are per operative diagnosis and very difficult to diagnose pre operatively. Here we present one such case with a combined ovarian and axial torsion of uterus. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 2 / Issue 16 / July-Dec, 2013 / 63-64 DOI: http://dx.doi.org/10.3126/njog.v8i2.9775